2017
DOI: 10.3390/md15070217
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of DNA Topoisomerase I Inhibitors with Low-Cytotoxicity Based on Virtual Screening from Natural Products

Abstract: Currently, DNA topoisomerase I (Topo I) inhibitors constitute a family of antitumor agents with demonstrated clinical effects on human malignancies. However, the clinical uses of these agents have been greatly limited due to their severe toxic effects. Therefore, it is urgent to find and develop novel low toxic Topo I inhibitors. In recent years, during our ongoing research on natural antitumor products, a collection of low cytotoxic or non-cytotoxic compounds with various structures were identified from marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In addition, in our previous study, flavonoids 1 – 3 , 5 , 7 , and 9 showed DNA topoisomerase I (Topo I) inhibitory activity at a concentration of 100 μM. Particularly flavonoids 1 and 2 still exhibited potent inhibitory activity, even at 5 μM [ 47 ]. In general, the flavonoids showed significant biological activities, which should be important pharmacodynamic ingredients of P. pulchellum .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in our previous study, flavonoids 1 – 3 , 5 , 7 , and 9 showed DNA topoisomerase I (Topo I) inhibitory activity at a concentration of 100 μM. Particularly flavonoids 1 and 2 still exhibited potent inhibitory activity, even at 5 μM [ 47 ]. In general, the flavonoids showed significant biological activities, which should be important pharmacodynamic ingredients of P. pulchellum .…”
Section: Discussionmentioning
confidence: 99%
“…In normal cell lines, EGCG does not have any cytotoxic effect, as tested by a viability assay [ 60 ]. EGCG has a complex mechanism of action, and it has several targets, such as nuclear factor kappa light-chain enhancer of activated B cells (NF-kB) [ 61 ], vascular endothelial growth factor (VEGF) [ 62 ] and hTopIB [ 51 ]. A significant inhibition of hTopoIB activity but not hTopII was observed through a relaxation assay [ 51 ].…”
Section: Natural Compounds With In Vitro and In Vivo Activity On Htopibmentioning
confidence: 99%
“…Molecular docking has been the major SB methodology to predict affinities to macromolecular targets, to interpret binding modes, and to assist in the design of drug leads. Several recent publications illustrate the application of the method to MNPs [ 127 , 128 , 129 , 138 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ], and some representative examples are here described.…”
Section: Computer-aided Drug Design (Cadd)mentioning
confidence: 99%
“…A collection of 138 structures from low-cytotoxic or non-cytotoxic coral-derived fungi and plants were docked to the central catalytic domain of the Topo I–DNA complex and the 27 molecules with the most favourable predicted interactions were evaluated in vitro. Among these, four compounds showed activity at 25 μM and two compounds were active at 5 μM [ 155 ].…”
Section: Computer-aided Drug Design (Cadd)mentioning
confidence: 99%